Clinical Performance of Narrow-Diameter Titanium-Zirconium Implants: A Systematic Review. Issue 2 (April 2017) - Badran, Zahi; Struillou, Xavier; Strube, Nicolas; Bourdin, David; Dard, Michel; Soueidan, Assem; Hoornaert, Alain
Abstract : Purpose: Implant-supported prosthetic rehabilitations are in constant augmentation in everyday dental practice. This is largely due to increasing demand from patients for fixed or implant-stabilized prosthesis, although they are frequently reticent to complex preimplant bone augmentation surgeries, whenever bone volume is lacking. Narrow-diameter implants (NDI; ⩽3.5 mm) have been developed to offer relatively simple implant solutions in challenging bone-deficient sites. However, concerns regarding their mechanical properties have been raised. Special titanium-zirconium material (Ti-Zr), with superior mechanical resistance, compared with pure titanium alloys has been introduced into the market. The purpose of this systematic review was to determine the available data on clinical performance of Ti-Zr NDI. Materials and Methods: A literature search of all available clinical articles dealing with Ti-Zr NDI has been carried out. After including only prospective clinical trials, 14 papers were retrieved for thorough reviewing. Conclusion: Short-term results from preliminary clinical reports are quite promising, although the number of published studies and the follow-up periods are still insufficient to determine the real benefit of this hybrid material compared with titanium, especially when using NDI.